ENGLISH MODULE FOR RAILWAY ENGINEERING: A NEED ANALYSIS - Armyta Puspitasari; Ainun Fikria; Edi Nyoto Setyo Marsusiadi; Septiana Widiastuti (Fakultas Ilmu Pendidikan Universitas Negeri Surabaya, 2024)
The purpose of this study was to determine the need analysis of English module for railway engineering. To know the students’ need, this study used a questionnaire and observation to collect the data then it described qualitatively. In listening skill, the students need about the monolog including with videos The procedure would be identifying the content of conversation; (2) In speaking, the students would need to work in pair in practicing the dialog, and the procedure was discussing and presenting the material; (3) In reading the text would include the vocabularied about railway building and construction context and the procedure was about reading and answering the questions based on the text. (4) In writing, the material should be about writing the railway track component. The procedure was writing paragraphs; (5) In vocabularies. The students’ need to learn about parts of speech, and the procedure was identifying the meaning based on the language context; (6) the length of the material in 100-200 words (intermediate); (7) The setting of teaching and learning process was in the class and at the laboratories/workshop; (8) The lecturers’ role should be Creating a pleasant atmosphere so that students are able to solve problems actively and are able to do their tasks well; and (9) The students’ role needs to discuss and participate actively during teaching ang learning process